Spring Forward, Don't Fall Back: The Effect of Daylight Saving Time on Road Safety - Bünnings, Christian; Schiele, Valentin (The Review of Economics and Statistics, 2021)
In this paper, we analyze the effect of light conditions on road accidents and estimate the long-run consequences of different time regimes for road safety. Identification is based on variation in light conditions induced by differences in sunrise and sunset times across space and time. We estimate that darkness causes annual costs of more than £500 million in Great Britain. By setting daylight saving time year-round, 8% of these costs could be saved. Thus, focusing solely on the short-run costs related to the transition itself underestimates the total costs of the current time regime.